Evaluation of competency-driven training for facilitators delivering a psychological intervention for children in Lebanon: a proof-of-concept study. (11th July 2022) - Jordans, M. J. D.; Steen, F.; Koppenol-Gonzalez, G. V.; El Masri, R.; Coetzee, A. R.; Chamate, S.; Ghatasheh, M.; Pedersen, G. A.; Itani, M.; El Chammay, R.; Schafer, A.; Kohrt, B. A.
Abstract: Aims: The mounting evidence for effective delivery of psychological interventions by non-specialists in low- and middle-income settings has led to a rapid expansion of mental health and psychosocial support trainings globally. As such, there is a demand for strategies on how to train and implement these services to attain adequate quality. This study aims to evaluate the added value of a competency-driven approach to training of facilitators for a group intervention for children with severe emotional distress in Lebanon. Methods: In a controlled before and after study, 24 trainees were randomly allocated to participate in either a competency-driven training (CDT) or training-as-usual (TAU) (1 : 1) for a psychological intervention for children with severe emotional distress. We assessed the change in demonstrated competencies, using standardised role-plays, before and after the training. Measures included the 13-item Working with children-Assessment of Competencies Tool (WeACT), the 15-item ENhancing Assessment of Common Therapeutic factors (ENACT) and the 6-item Group facilitation: Assessment of Competencies Tool (GroupACT). The trainer in the experimental arm used pre-training and during training competency assessment scores to make real-time adjustment to training delivery. Due to COVID-19 pandemic restrictions, all activities were done remotely. Results: CDT resulted in significantly better outcomes on increasing competencies on the WeACT (repeated measures analysis of variance; F (1, 22) = 6.49, p < 0.018) and on the GroupACT (Mann–Whitney U = 22, p < 0.003), though not statistically significant on the ENACT. There is no significant between-group difference on the reduction of harmful behaviours, mainly because both forms of training appear equally successful in eliminating such behaviours. Conclusions: This proof-of-concept study demonstrates the potential of CDT, using standardised assessment of trainee competencies, to contribute to better training outcomes without extending the duration of training. CDT can result in up to 18% greater increase in adequate competency, when compared to TAU. The study also yields recommendations for further enhancing the benefits of competency-driven strategies. A fully powered trial is needed to confirm these findings.